Biopassivation Method for the Preservation of Copper and Bronze Artefacts - Joseph, Edith (Frontiers in Materials, 2021)
A biopassivation method has been proposed as a new ecological and sustainable solution for preserving copper-based artefacts using selected microorganisms. This technology is based on the natural capacity of some fungi to form copper oxalates on the corroded surface of copper alloys. Existing unstable and pulverulent corrosion products are converted into an insoluble and chemically stable biopatina that provides the treated surfaces with a stabilization of the corrosion process and an aesthetically attractive green color. This treatment allows to stabilize the active corrosion induced for example by copper chlorides and to prevent green staining of surrounding materials (stone pedestal, wall…) due the leaching and loss of pulverulent and water-soluble corrosion products (i.e. copper sulfates). The behavior and performance of the proposed treatment have been followed during natural aging procedures, which have shown that this method stabilizes the corrosion process while having less chromatic variation compared to more traditional protective systems. The application protocol was then validated on real cases such as outdoor sculptures and archaeological objects. Based on these results, a ready-to-use kit is now proposed to conservators.